Peran Anonimitas Terhadap Perilaku Cyberbullying di Media Sosial - Muhammad Bintang Prakasa; Akhmad Luthfi Azhari; Ridho Agasi Putra; Konto Iskandar Dinata (CV. Doki Course and Training, 2026)
The study aims to determine the role of anonymity in cyberbullying behavior on social media, focusing on related aspects, namely psychological and social aspects. This study used a literature study method by collecting data sources from journal articles and books relevant to the research topic. The results obtained from this study indicate that anonymity plays a significant role in the occurrence of cyberbullying behavior on social media, and has serious impacts on the intended victims. Therefore, these findings require firm and strong action to address cyberbullying, especially from the government, law enforcement officials, and social media service providers.